2013
DOI: 10.1017/s1368980013000207
|View full text |Cite
|
Sign up to set email alerts
|

Trends in dietary intake in Switzerland, 1999 to 2009

Abstract: Objective: To assess nutrition trends of the Geneva population for the period 1999-2009. Design: Bus Santé Geneva study, which conducts annual health surveys in random samples of the Geneva population. Dietary intake was assessed using a validated FFQ and trends were assessed by linear regression. Setting: Population-based survey. Subjects: Data from 9283 participants (50 % women, mean age 51?5 (SD 10?8) years) were analysed. Results: In both genders total energy intake decreased from 1999 to 2009, by 2?9 % in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
(49 reference statements)
5
9
1
Order By: Relevance
“…The 'Bus Santé' is described elsewhere. 24 Briefly, the study started in 1993 and ever since, each year, a representative sample of non-institutionalised men and women aged 34-75 years was recruited from 1993 to 2009, and aged 18-85 from 2010 to 2014. Eligible participants were identified with a standardised procedure using a residential list annually established by the local government.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'Bus Santé' is described elsewhere. 24 Briefly, the study started in 1993 and ever since, each year, a representative sample of non-institutionalised men and women aged 34-75 years was recruited from 1993 to 2009, and aged 18-85 from 2010 to 2014. Eligible participants were identified with a standardised procedure using a residential list annually established by the local government.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were also asked to indicate the average serving size (smaller, equal or bigger) compared with the standard alcohol serving size, equal to 10 g of pure alcohol. 24 We excluded participants who did not answer all the questions about alcohol and also those who gave incoherent answers. Data derived from this FFQ have been used by several large worldwide consortium (eg, Nutricode 27 ) and published in high-impact journals.…”
Section: Data Collectionmentioning
confidence: 99%
“…Participants with missing data for education, age, weight, height, marital status, smoking habits and country of birth or nationality were excluded, as well as participants with extreme energy intakes (<850 or >4000 kcal/day) or implausible values for nutrient intake ( i.e. , >400 g/day of protein or >100 g/day fiber or >6000 mg/day calcium) as performed previously [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a downward trend in meat consumption (only women) and a stable energy intake were reported. The Bus Santé Geneva Study (Switzerland, 1999(Switzerland, -2009, participants' age: 34-74 years) showed that intakes of energy, SFA, PUFA, Ca and Fe decreased for both sexes, whereas intakes of carbohydrates (only women) and MUFA increased (assessed by semi-quantitative FFQ) (16) . Overall, other European surveys reveal more favourable trends in food consumption and nutrient intake compared with NEMONIT.…”
Section: Comparison With Other European Nutrition Surveysmentioning
confidence: 99%